2014
DOI: 10.1371/journal.pone.0102452
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Metabolic Heterogeneity in Head and Neck Tumors in Real Time: 2-DG Uptake Is Highest in Hypoxic Tumor Regions

Abstract: PurposeIntratumoral metabolic heterogeneity may increase the likelihood of treatment failure due to the presence of a subset of resistant tumor cells. Using a head and neck squamous cell carcinoma (HNSCC) xenograft model and a real-time fluorescence imaging approach, we tested the hypothesis that tumors are metabolically heterogeneous, and that tumor hypoxia alters patterns of glucose uptake within the tumor.Experimental DesignCal33 cells were grown as xenograft tumors (n = 16) in nude mice after identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
(111 reference statements)
1
23
0
Order By: Relevance
“…HNSCC cells also feature high levels of aerobic glycolysis. 10,11 In fact, some reports have already described that lactate, the end product of glycolysis, can be used as a prognostic tool in this type of tumor. Indeed, high levels of tumor lactate concentrations predict an increased metastasis formation 12 and a reduced overall and disease-free patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…HNSCC cells also feature high levels of aerobic glycolysis. 10,11 In fact, some reports have already described that lactate, the end product of glycolysis, can be used as a prognostic tool in this type of tumor. Indeed, high levels of tumor lactate concentrations predict an increased metastasis formation 12 and a reduced overall and disease-free patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our data are in line with several recent studies reporting diverse subsets of cancer cells with different metabolic requirements that reside within various tumor entities. 7,8 The co-existence of CSC subsets differing in their oxygen metabolism has also been suggested for established head and neck squamous cell carcinoma cell lines with hypoxia inducible factor 1 a (HIF-1a) as a major determinant. 9 Moreover, metabolically distinct subsets of CSCs have been found in relation to an epithelial-mesenchymal transition (EMT) phenotype.…”
mentioning
confidence: 99%
“…Theoretically, the hypodense necrotic zones on CT contrast images imply areas of hypovascularity and might harbor hypoxic cells, which could lead to the negative impact on nodal control as hypoxic cells are less radiosensitive (18). Nakajima et al (21) analyzed tumor cells grown as xenograft in nude mice after the identification of the metabolic response to hypoxia and found 2-deoxyglucose uptake in hypoxic regions of the tumors was approximately 2 times higher than in the whole tumor. They concluded that hypoxia is associated with increased intratumoral metabolic heterogeneities on 18 F-FDG PET.…”
Section: Discussionmentioning
confidence: 99%